How Can Questions Encourage Engagement with Retirement Planning? A Good Question - Kronrod, Ann (Journal of Consumer Research, 2026)
Abstract We spend nearly a third of our lives in retirement, sometimes as long as the time we work and save for it. Yet, despite the severe personal, economic, and national consequences of under-funded retirement accounts, people often procrastinate and avoid retirement planning. Current efforts to encourage planning achieve limited success, partly because individuals do not think about retirement, often until it is too late. Addressing this challenge, we explore how language can influence retirement planning behaviors by encouraging more concrete thinking about the topic. Drawing on psycholinguistic research suggesting that questions encourage concrete thinking, we propose that phrasing communication as questions enhances engagement with retirement planning by eliciting more concrete thinking about retirement. Across six studies, we demonstrate the impact of questions on engagement with retirement planning. These include a text analysis of a large dataset, three field experiments with diverse populations and conditions, and two online studies confirming that questions outperform statements in retirement-related communication by promoting more concrete thinking and eliciting more engagement with the topic. Given that most retirement communication is phrased as statements, this research offers managers a low-cost solution to improve retirement planning and funding, with significant individual and national benefits.